Sixteen : short stories by outstanding writers for young adults - Gallo, Donald R. (New York : Delacorte Press, 1984)
Sixteen short stories, dealing with teenage concerns, written especially for this collection by well-known authors of young adult novels such as the Mazers, M.E. Kerr, Robert Cormier, Bette Greene, and Richard Peck. Biographical sketches for each author are included, as well as follow-up activities for the reader.
Child Study Children's Book Committee.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
6.1
7.0
5-8
Keywords: Short stories; Short stories